The Hegemony of Global Politics: News Coverage of Climate Change in a Small Country - Horta, Ana (2017)
Researching media coverage of climate change may shed light on the different configurations of global and domestic factors affecting journalism and politics. This article analyzes climate change coverage in Portugal from 2007 to 2014 in comparison with 14 other countries. It shows that the Portuguese press tends to reproduce the global political agenda on climate change, mainly focusing on international events associated with global political decision-making processes, instead of providing a domesticated coverage, as observed in other countries. National and local levels of action are thus obscured. The interplay between global and domestic factors—including characteristics of Portugal’s press and politics, such as national political leaders’ lack of mobilization and communication on climate change, media’s deference to powerful sources, and reliance on international news feeds—creates the conditions for global politics to play an hegemonic role in media representations, which is likely to influence public engagement with climate change.